Improvement of logistic activity in control system an industrial enterprise - Мishura, V.; Volodchenko, V. (Економічний вісник Донбасу, 2018)
In the article the analysis of forming of conceptual positions of relatively logistic management is conducted by sale activity as to important component part of control system by an enterprise. The role of logistic of sale is certain in activity of industrial enterprise. Fundamental conceptions of logistic are presented. It is well-proven that advantages of logistic management is providing of integrating, system, to the management complexity by resource and informative streams, that provides synchronization of business processes and case (planning, organizations, motivations, control, co-ordination) frame, creates new possibilities of height of valueadded and providing of competitiveness of enterprise. У статті проведено аналіз формування концептуальних положень щодо логістичного управління збутовою діяльністю як важливого складника системи управління підприємством. Визначено роль логістики збуту в діяльності промислового підприємства. Представлено фундаментальні концепції логістики. Доведено, що перевагами логістичного управління є забезпечення інтегрованості, системності, комплексності управління ресурсними та інформаційними потоками, що забезпечує синхронізацію бізнес-процесів і моделі управління (планування, організації, мотивації, контролю, координації), створює нові можливості зростання доданої вартості та забезпечення конкурентоспроможності підприємства. В статье проведен анализ формирования концептуальных положений относительно логистического управления сбытовой деятельностью как важной составной части системы управления предприятием. Определена роль логистики сбыта в деятельности промышленного предприятия. Представлены фундаментальные концепции логистики. Доказано, что преимуществами логистического управления является обеспечение интегрированности, системности, комплексности управления ресурсными и информационными потоками, которое обеспечивает синхронизацию бизнес-процессов и модели управления (планирования, организации, мотивации, контроля, координации), создает новые возможности роста добавленной стоимости и обеспечения конкурентоспособности предприятия.